Recognising and valuing the cultural significance of biodiversity in coastal marine territories through plural knowledges systems: Advancing the mission of the intercultural university of the peoples - Fátima Alves; Diogo Guedes Vidal; Rosário Rosa; Helena Freitas; Hermano Castro (Societal Impacts, 2025)
Contemporary societies are rich in social, cultural, epistemological, and biophysical diversity, occupying territories that call for recognition and a voice. This recognition is crucial for understanding the social, cultural, and political factors that drive environmental degradation and exacerbate climate change impacts. The Intercultural University of Peoples (IUP) is in the process of being established in Brazil to address this need, leading to the development of the action research project ''Promoting the Cultural Value of Biodiversity and Sustainability in Coastal Marine Territories''. This project emphasises the value of socio-biodiversity through local knowledges, especially that of traditional communities. Our goal is to develop tailored policies and programmes that support sustainability, health, and the rights of traditional communities, while aligning with IUP’s mission. A key part of our approach is fostering a participatory ethos in coastal communities to drive sociobiodiversity conservation and climate action. Through this initiative, we aim to contribute to sustainable development grounded in the values and knowledges of local populations and to further the mission of IUP.